Invited author response to editorial commentary: hypoalbuminemia in patients undergoing transcatheter aortic valve replacement: culprit or surrogate? - Gassa, Asmae; Borghardt, Jan Hendrik; Maier, Johanna; Michel, Max; Mader, Navid; Baldus, Stephan; Wahlers, Thorsten (Journal of Thoracic Disease, 2019)
With great interest, we read the editorial commentary by Drs. Aranda-Michel, Bianco, Kilic and Sultan. Their commentary highlights the many factors possibly leading up to and interacting with hypoalbuminemia. Low albumin level could be used as a possible indicator of anemia, limited daily living, and heavy smoking in elderly patients which we confirmed in the characterization of our patient cohort such as dialysis requirements, chronic obstructive pulmonary disease (COPD), and a worse New York Heart Association classification.